Design of all-optical AND logic gate at 20 Gb/s based on SOA-MI with optimum injection current and length of TWA-SOA - Oliveira, Jackson Moreira; Silva, Hudson Afonso Batista; Sousa, Fabio Barros; Oliveira, Jorge Everaldo; Costa, Marcos Benedito Caldas (Scientia Plena, 2019)
The manuscript presents Design of All-optical AND logic gate at 20 Gb/s using Semiconductor Optical Amplifier based on Michelson Interferometer (SOA-MI). The paper shows a comprehensive numerical simulation using OptiSystem software to examine two-input logical function (with 8-bit). Used the CW Laser, Dual Directional Coupler, 100% reflective linear Fiber Bragg Grating (FBG) and Optical Filter, and investigated the optimum injection current and length of the TWA-SOA for obtaining the best result Q-Factor and BER based on Eye diagram to logic gate. To the best of our knowledge, this is the first report on a numerical simulation of an All-Optical AND logic gate at 20 Gb/s with SOA-MI using co-propagating, structure with results ensure good performance of the proposed design.